SIMULASI RANCANG BANGUN PEMANTAUAN SUHU RUANG DENGAN MULTI SENSOR LM35DZ - Susilawati Susilawati; Yayan Prima Nugraha; Adhi Rizal (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2017)
This laboratory research aims to develop a proper room temperature control system in real time and efficient use the concept of simulation. In the first stage experiments were carried out to simulate temperature variations, in a room consisting of 8 point measurements using the LM35 temperature sensor. Then some room temperature conditions are also generated virtually, so that when certain conditions DC motor rotates to move the fan. In the final stages, the temperature is shown in graphical form and displays the temperature distribution waveform in LabVIEW in real-time. Based on the experimental results, the LM35 temperature sensor is able to detect the temperature in real-time in eight different positions. Once the temperature is detected, the LabVIEW software can display temperature variations in three different conditions in real-time, there are comfortable, almost comfortable, and less comfortable. Then, if the temperature detected is in the less comfortable category, the DC motor is moving. Keywords: temperature distribution, LM35 sensor, DC motor, LabVIEW.